Increase of Carotid Intima-Media Thickness and Reduction of Carotid Artery Lumen Diameter in Breast Cancer Patient Before and After Chemotherapy - Kartika, Inez; Asih, Made Widhi; Martadiani, Elysanti Dwi; Anandasari, Pande Putu Yuli; Patriawan, Putu; Widiana, I Gde Raka (JBN (Jurnal Bedah Nasional), 2022)
Background: Increasing number of cancer survivor motivates clinical practitioner to focus on chronic effect of chemotherapy agent, especially those with vascular toxicity effect, which may attenuate the incidence of thrombosis and atherogenesis. Ultrasonography examination on carotid intima media thickness (C-IMT) provides acurate result in evaluating atherosclerotic. The purposes of this research are to find out any structural changes of carotid artery, especially atheroclerosis changes in breast cancer patient after chemoteraphy. Methods : Analytic cross sectional study using a pre post test group design in breast cancer patients. Eligible subjects undergo carotid ultrasonography examination prior to chemoteraphy and after they had completed the 3 cycles of chemoteraphy for the second exam. The examination was perfomed with the same USG machine, high frequency linier transducer (>7mHz) in B-mode under the auspecies of  two reputable radiologist consultant. Results: Total patients are 26, mean of age (year) is 47.15 ± 8.11. Most dominant histopathology finding is invasive carcinoma nonspecific type, in 24 patients (92.4%) and the disease stage is in stadium III in 14 patients (53.9%). Mean C-IMT (mm) prior chemotherapy is 0.51 ± 0.06 and after chemotherapy is 0.58 ± 0.05,  there is an increase of 0.07 ± 0.06 (p<0.0001). Carotid artery lumen diameter (mm) before chemotherapy is 4.05 ± 0.66 and after chemotherapy is 3.90 ± 0.73, so there is a decrease of 0.16 ± 0.40 (p =0.057). Conclusion: There is a statistically significant increase in intima media thickness of carotid wall of breast cancer patients after chemotherapy, consisted with chemoteraphy induced atherosclerosis.